Least limiting water range and crop yields as affected by crop rotations and tillage - Olibone, D. [UNESP]; Encide-Olibone, A. P. [UNESP]; Rosolem, Ciro Antonio [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
Crop rotation and the maintenance of plant residues over the soil can increase soil water storage capacity. Root access to water and nutrients depends on soil physical characteristics that may be expressed in the Least Limiting Water Range (LLWR) concept. In this work, the effects of crop rotation and chiselling on the soil LLWR to a depth of 0.1 m and crop yields under no-till were studied on a tropical Alfisol in São Paulo state, Brazil, for 3 yr. Soybean and corn were grown in the summer in rotation with pearl millet (Pennisetum glaucum, Linneu, cv. ADR 300), grain sorghum (Sorghum bicolor, L., Moench), congo grass (Brachiaria ruziziensis, Germain et Evrard) and castor bean (Ricinus comunis, Linneu) during fall/winter and spring, under no-till or chiselling. The LLWR was determined right after the desiccation of the cover crops and before soybean planting. Soil physico-hydraulic conditions were improved in the uppermost soil layers by crop rotations under zero tillage, without initial chiselling, from the second year and on, resulting in soil quality similar to that obtained with chiselling. In seasons without severe water shortage, crop yields were not limited by soil compaction, however, in a drier season, the rotation with congo grass alone or intercropped with castor resulted in the greatest cover crop dry matter yield. Soybean yields did not respond to modifications in the LLWR.
Keywords: Soil water; penetration resistance; soil compaction; biological sub soiling